Memnoniella and Stachybotrys species from Musa acuminata - Photita W. (2014)
Memnoniella subsimplex and five species of Stachybotrys species are reported from Musa acuminata in Hong Kong and Thailand. Stachybotrys suthepensis sp. nov., found on decaying petioles, is described, illustrated and compared with similar species. It is characterized by conidia that are ellipsoid to cylindrical, rounded at both ends, olivaceous-brown to brown, verruculose and 7-9 x 3-6 μm.